2020
DOI: 10.1016/j.carbon.2019.10.053
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial two-dimensional oxide enhances photocatalytic activity of graphene/titania via electronic structure modification

Abstract: The photocatalytic activity of titania nanoparticles deposited on epitaxial graphene is proven to be significantly affected by the substrate on which graphene is supported. In particular, it has been revealed that the addition of a two-dimensional TiO1.5 layer sandwiched between graphene and the supporting metal induces a p-doping of graphene itself and a consistent shift in the Ti d states.These modifications in the electronic structure are compatible with the reduction of the probability of charge carrier re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 76 publications
1
2
1
Order By: Relevance
“…If the decreasing of the photoemission intensity of Ir surf was caused by other effects such as screening due to sulfur atoms adsorbed on Gr, then also the bulk component would have the same behavior, which is not the case. The fact that we have intercalation already at room temperature is interesting and not common in the case of Gr, for which the temperature usually necessary to promote and achieve the intercalation of atoms under a complete layer of Gr is of the order of at least 400 K. , In particular, this is quite different from what was recently reported where the temperature to initiate the S intercalation under graphene is 450 K.…”
Section: Resultscontrasting
confidence: 63%
“…If the decreasing of the photoemission intensity of Ir surf was caused by other effects such as screening due to sulfur atoms adsorbed on Gr, then also the bulk component would have the same behavior, which is not the case. The fact that we have intercalation already at room temperature is interesting and not common in the case of Gr, for which the temperature usually necessary to promote and achieve the intercalation of atoms under a complete layer of Gr is of the order of at least 400 K. , In particular, this is quite different from what was recently reported where the temperature to initiate the S intercalation under graphene is 450 K.…”
Section: Resultscontrasting
confidence: 63%
“…Combining the GQDs on the surface of hybrid photocatalysts, the absorption of visible light in the hybrid systems increased because of the intrinsic light absorption by the pGQDs and rGQDs in the visible domain and the effects of doping π electrons from sp 2 carbon on graphene (Figure S11). The steady-state photoluminescent (PL) spectra (under 270 nm excitation; Figure b) indicated that the deposition of GQDs promoted the separation of photoexcited electrons and holes in the HT/PDDA/pGQDs and HT/PDDA/rGQD hybrid systems, which is consistent with the conclusion of the TiO 2 and graphene hybrid systems in the previous report. , …”
Section: Resultssupporting
confidence: 89%
“…29 The steady-state photoluminescent (PL) spectra (under 270 nm excitation; Figure 4b) indicated that the deposition of GQDs promoted the separation of photoexcited electrons and holes in the HT/PDDA/pGQDs and HT/PDDA/rGQD hybrid systems, which is consistent with the conclusion of the TiO 2 and graphene hybrid systems in the previous report. 40,41 TPV spectra of various as-prepared photocatalysts were obtained to characterize the dynamic separation and transport of photoexcited charge carriers in the hybrid systems. Owing to the unique nanostructure of these photocatalysts, the hollow spherical TiO 2 frameworks provided photogenerated charge carriers, and the TPV spectra primarily depicted the photoinduced carrier transfer dynamics on the TiO 2 surface.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Moreover, the Coulomb interaction potentiation in 2D photocatalysts leads to high exciton binding energy, which is adverse to the disseverance of photoexcited carrier pairs . To solve these issues, apart from finding novel 2D photocatalysts, other strategies have been considered, such as heteroatom doping, introducing defects, and constructing heterojunctions. …”
Section: Introductionmentioning
confidence: 99%